2022
DOI: 10.1038/s41467-022-32061-1
|View full text |Cite
|
Sign up to set email alerts
|

TRIM28-dependent SUMOylation protects the adult ovary from activation of the testicular pathway

Abstract: Gonadal sexual fate in mammals is determined during embryonic development and must be actively maintained in adulthood. In the mouse ovary, oestrogen receptors and FOXL2 protect ovarian granulosa cells from transdifferentiation into Sertoli cells, their testicular counterpart. However, the mechanism underlying their protective effect is unknown. Here, we show that TRIM28 is required to prevent female-to-male sex reversal of the mouse ovary after birth. We found that upon loss of Trim28, ovarian granulosa cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 107 publications
6
31
0
Order By: Relevance
“…This study demonstrated the plasticity of the adult ovary and the crucial role played by FOXL2 in this process. More recently, a similar role in ovarian sex maintenance was discovered for TRIM28, which we show to be recruited on chromatin together with FOXL2 and to regulate the sex-specific SUMOylation profile of ovarian-specific genes through its E3-SUMO ligase activity [8].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…This study demonstrated the plasticity of the adult ovary and the crucial role played by FOXL2 in this process. More recently, a similar role in ovarian sex maintenance was discovered for TRIM28, which we show to be recruited on chromatin together with FOXL2 and to regulate the sex-specific SUMOylation profile of ovarian-specific genes through its E3-SUMO ligase activity [8].…”
Section: Introductionsupporting
confidence: 71%
“…We then scanned the 1 Mb gene desert upstream of Sox9, which was previously found to contain cis-regulatory elements essential for Sox9 expression in Sertoli cells [38,39]. As previously shown [8,27], neither TESCO nor enhancer 13, were significantly bound by FOXL2 at any point during ovarian development. Instead, we observed a dynamic binding of FOXL2 in other known Sox9 enhancers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SUMOylation has already proven a role in adrenocortical development with the unSUMOylatable SF-1 2KR/2KR model, which results in adrenal cells expressing gonadal markers 21 . In ovaries which share a common foetal origin with adrenals, SUMOylation by the E3 SUMO-ligase activity of TRIM28, is essential for maintenance of granulosa cell fate at the expense of Sertoli-like identity 58 , whereas SENP1 presence in stromal cells is necessary for proper oocyte maturation and ovulation 59 . From a broader perspective, our study belongs to a growing corpus of evidence associating SUMOylation with coordination of differentiation in different tissues and cell types such as white and brown adipose tissue 15 , 17 , 60 , induced pluripotent stem cells 16 , or intestine 18 .…”
Section: Discussionmentioning
confidence: 99%
“…For IF analysis, tissue sections were deparaffinized, followed by antigen retrieval with 10 mM citrate buffer (pH 6) in the Histo5 apparatus (Milestone, Brondby, Denmark) for 20 min, as previously described [ 127 , 148 ]. Sections were then blocked with 10% donkey serum (Sigma-Aldrich) or 1/1000 anti-goat IgG (Thermofisher, Waltham, MA, USA), and incubated (4 °C, overnight) with the following primary antibodies: monoclonal mouse anti-PCNA (Sigma-Aldrich P8825, 1/500), anti-phospho-gH2Ax (Ser139 clone JBW301, Sigma Aldrich 05-636, 1/500), anti-COUPTFII (RD systems PP-H7147-00, 1/400), a-tubulin (Sigma Aldrich T9026, 1/1000), monoclonal rat anti-phosphorylated-Histone H3 (Ser10, Sigma Aldrich H9908, 1/400), anti-Tra98 (Abcam ab82527, 1/400), polyclonal guinea pig anti-PADI6 (1/500), polyclonal goat anti-Sox9 (RD systems AF3075, 1/300), polyclonal rabbit anti-FoxL2 (homemade [ 149 ], 1/300), anti-AMH (gift from N DiClemente, 1/300), anti-Lin28a (ProteinTech 11724, 1/400), anti-connexin-43 (Sigma Aldrich C6219, 1/500), and anti-a Smooth muscle actin (SMA) (Abcam ab124964, 1/500). Sections were then incubated with donkey or goat secondary antibodies conjugated with Alexa Fluor 555, 488, or 649 (Thermofisher, 1/1000) at room temperature for 30 min, followed by Hoechst staining.…”
Section: Methodsmentioning
confidence: 99%